Preliminary results of the archaeological surveys conducted at the Álamo Roman Dam (Alcoutim, Portugal) during the years of 2006 and 2007 - Cardoso, João Luís (2016)
The remarkable Roman Álamo Dam identified by Estácio da Veiga in 1877 was investigated between 2006 and 2007 by a team directed by the first author and with ongoing participation of the second. The archaeological works performed close to the upstream wall of the dam allowed showing the remarkable height of the construction, currently partially buried in the sediments accumulated at the bottom of the old reservoir. The remains contained several fragments of amphorae whose typological characterization suggests that the structure would functioned at least between the 3rd and the 5th centuries d.C., although over the past years it has been already completely silted, thus constituting one swampy zone to where they would be thrown objects no longer in use, including the fragments of more modern amphorae. Regarding this issue, it is noteworthy that this will be the first work of this kind performed in Portugal.